PERANCANGAN MESIN PRESS BALER HORIZONTAL UNTUK PENINGKATAN PRODUKTIVITAS PETERNAK SAPI KABUPATEN BONE - Djamaluddin, Fauzan; Renreng, Ilyas; Takdir, Takdir (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
Cattle breeders in Bone district usually have a shortage of cattle feed in the form of grass and hay in the dry season. Usually grass or straw is not stored in a warehouse because of limited space. Cattle supply is adjusted when daily needs are not based on each month or year. Cattle farmers in Bone district still carry out the process of transporting grass or straw naturally so that the capacity of the feed being transported is small and requires a long time. To get 5-10 kg of cattle feed, it takes a day while the needs of cattle are 60-120 kg per day. To increase the productivity of breeders in the fattening process, a cattle feed press machine technology is needed. Therefore, through the Unhas Community Service Program Campus Intellectual Product Development Program (PPMU-PPUPIK),, we propose the technology of cow feed press machines to increase the productivity of cattle farmers in Bone Regency